2010
DOI: 10.1111/j.1524-4733.2010.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Cost-Effectiveness Analyses Inform Reimbursement Decisions for Oncology Medicines in Canada? The Example of Sunitinib for First-Line Treatment of Metastatic Renal Cell Carcinoma

Abstract: This demonstrates that the cost-effectiveness ratio is only one of many factors that affect an access decision in oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…Out of the 20 congress abstracts concerning first-line mRCC treatment, 16 were based on a same model or similar model structure presented in more detail in the full articles [14][15][16].…”
Section: Cost-effectiveness Studies Of New Therapies For Mrccmentioning
confidence: 99%
“…Out of the 20 congress abstracts concerning first-line mRCC treatment, 16 were based on a same model or similar model structure presented in more detail in the full articles [14][15][16].…”
Section: Cost-effectiveness Studies Of New Therapies For Mrccmentioning
confidence: 99%
“…As such, both the costing and the cost-utility analysis work are novel. Because improving care of remote-and rural-dwellers continues to be a high priority for governments around the world (24-26), our results are relevant for decision makers, particularly given that this clinic seems cost-effective by accepted standards, and are markedly lower than for other interventions in common use for patients with (27,28) and without CKD (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…These ICERs are below ICER estimates for a 21-GEP assay 59,60 and cancer drugs that were recently recommended for adoption. 61,62 The clinical benefit of 0.28 LY is comparable to several recently approved drugs for metastatic disease. [63][64][65][66] The budget impact analysis shows that adoption of the 2000-GEP testing would lead to total incremental cost of $36.2 million per year.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when these three groups of parameters were negatively modified by approximately 35% (Figure 2d) the ICER became well above ranges of a number of cancer treatments recently approved for funding in Canada 61,62 and the 2000-GEP-based strategy may no longer deemed a cost effective use of resources. Our value-ofinformation analysis demonstrated that there is a significant societal benefit from future research that can better characterize these three groups of parameters.…”
Section: Discussionmentioning
confidence: 99%